Adaptive radio for multimedia wireless links. - Chien, C. (IEEE Journal on selected areas in communications)
The quality of wireless links suffers from time-varying channel degradations such as interference, flat-fading, and frequency-selective fading. Current radios are limited in their ability to adapt to these channel variations because they are designed with fixed values for most system parameters such as frame length, error control, and processing gain. The values for these parameters are usually a compromise between the requirements for worst-case channel conditions and the need for low implementation cost. Therefore, in benign channel conditions these commercial radios can consume more battery energy than needed to maintain a desired link quality, while in a severely degraded channel they can consume energy without providing any quality-of-service (QoS). While techniques for adapting radio parameters to channel variations have been studied to improve link performance, in this paper they are applied to minimize battery energy. Specifically, an adaptive radio is being designed that adapts the frame length, error control, processing gain, and equalization to different channel conditions, while minimizing battery energy consumption. Experimental measurements and simulation results are presented to illustrate the adaptive radio's energy savings